2023
DOI: 10.21037/jtd-23-494
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis based on DNA methylation data identified in lung adenocarcinoma subgroups with different immune characteristics and clinical outcomes

Abstract: Background DNA methylation can be used to predict clinical outcomes and improve the classification of tumors. The present study aimed to develop a new lung adenocarcinoma (LUAD) classification system according to the immune cell gene-related methylation sites and to reveal the survival outcomes, clinical characteristics, immune cell infiltration, stem cell characteristics, and genomic variations of each molecular subgroup. Methods The DNA methylation sites of LUAD sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…DNA methylation is a major epigenetic modification and plays an important roles in carcinogenesis and progression (Fu et al 2022 ); and recent evidence has showed that driver methylation rather than passenger methylation are associated with cancer progression and prognosis (Pfeifer 2018 ; Kalari and Pfeifer 2010 ). Previous studies have suggested that LUAD could be stratified into different molecular subtypes by methylation signatures (Guidry et al 2022 ; Yu et al 2023 ; Smet 2023 ). However, there is lack of evidence on studying the driver methylation-based subtype of LUAD.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is a major epigenetic modification and plays an important roles in carcinogenesis and progression (Fu et al 2022 ); and recent evidence has showed that driver methylation rather than passenger methylation are associated with cancer progression and prognosis (Pfeifer 2018 ; Kalari and Pfeifer 2010 ). Previous studies have suggested that LUAD could be stratified into different molecular subtypes by methylation signatures (Guidry et al 2022 ; Yu et al 2023 ; Smet 2023 ). However, there is lack of evidence on studying the driver methylation-based subtype of LUAD.…”
Section: Introductionmentioning
confidence: 99%